The impact of COVID‐19 on obesity services across Europe: A physician survey. Issue 5 (13th July 2021) - Nather, Katrin; Bolger, Fiachra; DiModica, Laurie; Fletcher‐Louis, Mary; Salvador, Javier; Pattou, François; Panton, Ulrik Haagen; Cancino, Ana‐Paula
Summary: Obesity is a risk factor for severe complications from coronavirus disease 2019 (COVID‐19). During the COVID‐19 pandemic in Spring 2020, many clinics and obesity centers across Europe were required to close. This study aimed to determine the impact of COVID‐19 on the provision of obesity services across 10 European countries via a survey of physicians (n = 102) specializing in treating persons with obesity (PwO). In total, 62–95 out of 102 physicians reported that COVID‐19 affected obesity‐related services, with cancellations/suspensions ranging from 50% to 100% across the 10 countries. Approximately 75% of cancellations/suspensions were provider‐ rather than patient‐initiated. A median increase of 20%–25% in waiting times was reported for most services across the countries. When services resume, 87 out of 100 physicians consider factors influencing down‐stream patient outcomes as the most relevant factors for prioritizing interventional treatment. Responses showed that 65 out of 102 and 36 out of 102 physicians believed it (highly) likely that a change in treatment guidance will occur to prioritize earlier interventional treatment for the management of PwO, by either using bariatric surgery or pharmacotherapy, respectively. Results from this study provide important learnings, such as opportunities for, and discrepancies in, the provision of alternative care in light of services cancellations or delays, which may be important for the future management of obesity, especially during future waves of COVID‐19 or other infectious pandemics.